The impact of the COVID-19 pandemic on the mental health of young people: policy responses in European countries - European Education and Culture Executive Agency (European Commission) (Publications Office of the European Union, 2022)
The impact of the COVID-19 pandemic on the mental health of young people has been significant. Extended periods of lockdowns have disrupted their lives in many respects. The physical closure of schools, the suspension of in-person social and recreational activities and the isolation imposed by confinements have taken a toll on young people’s mental health. The report analyses the policy response given by public authorities in European countries to this emergency. It identifies the main factors affecting young people’s mental health during the pandemic and develops a detailed overview of the policies, initiatives and programmes established to address them. It also offers examples of good practices and, on this basis, suggests future directions in policy-making. The report covers the period from March 2020 to March 2022 and includes 32 countries. Information was provided by the National Correspondents of the Youth Wiki, Europe’s online encyclopaedia of national youth policies. The main objective of the Youth Wiki is to support evidence-based European cooperation in the field of Youth. It does so by providing information on national policies in support of young people – in a user-friendly and continuously updated way. The Youth Wiki is coordinated by the European Education and Culture Executive Agency and accessible at.